2013
DOI: 10.1111/ggi.12122
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Index in Europeans: Association with determinants of health

Abstract: Aim The Frailty Index (FI) summarizes differences in health status within individuals, and the determinants of health drive that variability. The aim of the present study was to investigate the influence of education, income, smoking, alcohol intake, and parental longevity on the FI variability in subjects of the same chronological age group. Methods Analyses were based on a 40-item FI based on the first wave of the Survey of Health, Ageing and Retirement in Europe (SHARE, http://www.share-project.org/), inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 43 publications
(70 reference statements)
6
34
0
1
Order By: Relevance
“…For example, an individual's wealth and the level of neighbourhood deprivation impacts on frailty and mortality but the size and direction of the impact may differ between the sexes (Gu et al, 2009;Lang et al, 2009;Major et al, 2010;Romero-Ortuno, 2014;Woo et al, 2005). Factors such as marital status, education level and social supports have all been reported to impact on male and female frailty (Andrew et al, 2008;Gorman and Read, 2006;Gu et al, 2009;Szanton et al, 2010;Woo et al, 2005).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…For example, an individual's wealth and the level of neighbourhood deprivation impacts on frailty and mortality but the size and direction of the impact may differ between the sexes (Gu et al, 2009;Lang et al, 2009;Major et al, 2010;Romero-Ortuno, 2014;Woo et al, 2005). Factors such as marital status, education level and social supports have all been reported to impact on male and female frailty (Andrew et al, 2008;Gorman and Read, 2006;Gu et al, 2009;Szanton et al, 2010;Woo et al, 2005).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…1 Cigarette smoking has been shown to be one of the major causes of a wide spectrum of age-related health outcomes. 9 However, its association with the development of frailty is not yet well-established, and reported findings were inconsistent: several cross-sectional studies reported that smoking was associated with being less frail, [10][11][12] while most prospective cohort studies asserted that baseline smoking status was predictive of significantly accelerated progression of frailty at followup. 4,13,14 In addition, the mechanisms underlying the potential linkage between smoking and frailty yet remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A couple of studies investigated the health deficit index (frailty index) using the SHARE data (Romero-Ortuno and Kenny, 2012;Harttgen et al, 2013, Theou et al, 2013Romero-Ortuno, 2014). 2 These studies focused mainly on the association of health deficits with mortality as well as with several socioeconomic indicators and on comparing health deficits of Europeans and citizens of selected developing countries.…”
Section: Introductionmentioning
confidence: 99%